Analysis of COVID-19 Antibodies in Patients Who Have Been Vaccinated With Non-Vaccinated Patients with Confirmed COVID-19 Life - Hutabarat, Mustika Sari H; Lubis, Agnes Felicia; Sinaga, Hotman (Medical Laboratory Technology Journal, 2024)
COVID-19 immunization is a government initiative to prevent transmission and reduce the incidence of disease and death associated with the SARS-CoV-2 virus. Although the SARS-CoV-2 virus is no longer a significant threat, older adults with comorbidities or people who are immunosuppressed should remain vigilant by maintaining a distance of at least one meter from others, covering their mouths with their elbows when coughing or sneezing, washing their hands regularly, and wearing masks. However, many groups oppose vaccination for various reasons, including the perception that the COVID-19 vaccine is less effective and efficient in preventing SARS-CoV-2 virus infection. This study compared COVID-19 antibody titers in participants who had arrived, without mentioning the vaccine brand, with those who had not yet arrived but had a history of SARS-CoV-2 infection. This study design used a cross-sectional study; the number of samples in the study was 34, the location of this study was the Palembang Public Health Laboratory Center, and the statistical test in the study used the Independent T-test. The study results indicate that the mean antibody titer in the vaccinated group was 98.123. In contrast, in the unvaccinated group, it was 70.641, demonstrating a statistically significant difference with a p-value of 0.000. Further research suggests whether there is a relationship between antibody titers in subjects who have been vaccinated for the second and third time with a history of exposure to the COVID-19 virus.